The Quizizz Application for Improving Mentally Retarded Students' Vocabulary - Syamsun, Tosi Rut; Syafrizal, Syafrizal; Pahamzah, John (Universitas Nurul Jadid, 2023)
This study was to research students’ vocabulary for using the Quizizz application in a special need school for mentally retarded students and how Quizizz applications used by teachers. To determine if the Quizizz app has an effect on mentally retarded students' vocabulary ability. These studies employed a quantitative research methodology with an experimental design that utilized a single organization for the pretest and posttest. The twenty test takers were all students and made up the population. Due to the fact that this pattern checks all college students, a total of 20 persons, it is a saturated pattern. Descriptive facts, prerequisite check assessment, and speculation testing make up the information series approach. Following the use of the Quizizz program, a code value reflecting pre- and post-test data on students' vocabulary proficiency was produced from the test results. 0.253 > 0.05. Similarly, at a critical threshold & it; (0.000 0.05), H0 and H1 are also rejected. These results imply that the ninth-grade Quizizz program has an impact on how pupils communicate.